2002
DOI: 10.1029/2001ja000184
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of ULF waves through the ionosphere: Analytic solutions for oblique magnetic fields

Abstract: [1] The propagation of ultra low frequency (ULF; 1-100 mHz) waves from the magnetosphere to the ground is examined in the presence of oblique background magnetic fields. The problem is developed analytically for a thin sheet ionosphere, neutral atmosphere, and perfectly conducting ground. The cold plasma, ideal magnetohydrodynamic (MHD) Alfvén wave modes are assumed to propagate in the MHD medium above the ionosphere. A reflection and wave mode conversion coefficient matrix (RCM) is derived which describes mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 30 publications
0
76
0
Order By: Relevance
“…After this initial period, the problem has also been studied for more general geometries of the background magnetic field (see, e.g., Leonovich and Mazur, 1991;Alperovich and Fedorov, 1993;Sciffer and Waters, 2002;Sciffer et al, 2004Sciffer et al, , 2005. Below we present a model and numerical results for the problem of magnetohydrodynamic wave transmission through and reflection from the ionosphere within a more realistic "thick ionosphere" model (Knudsen et al, 1992).…”
Section: Model Calculationsmentioning
confidence: 99%
“…After this initial period, the problem has also been studied for more general geometries of the background magnetic field (see, e.g., Leonovich and Mazur, 1991;Alperovich and Fedorov, 1993;Sciffer and Waters, 2002;Sciffer et al, 2004Sciffer et al, , 2005. Below we present a model and numerical results for the problem of magnetohydrodynamic wave transmission through and reflection from the ionosphere within a more realistic "thick ionosphere" model (Knudsen et al, 1992).…”
Section: Model Calculationsmentioning
confidence: 99%
“…As an example, Hebden et al (2005) observed harmonics up to almost 5 Hz from magnetometer data obtained from Sodankylä, Finland. These observations can be modeled using the equations in a tilted magnetic field geometry such as those introduced by Sciffer and Waters (2002). While this earlier work considered a uniform plasma density above the ionosphere, to study the IAR we can include a density profile of the form…”
Section: Effects Of Hall Conductance On the Iarmentioning
confidence: 99%
“…For oblique magnetic field dip angles, the degeneracy between the two perpendicular directions is broken, since waves with wave vectors in the latitudinal direction, in the plane of the dipole field, differ from those in the longitudinal direction. Sciffer and Waters (2002) and Sciffer et al (2004) have analyzed the reflection and mode conversion of Alfvén and fast mode waves in the presence of oblique magnetic fields. They find a strong dependence on dip angle, especially for longitudinal propagation.…”
Section: Effects Of Hall Conductance On the Iarmentioning
confidence: 99%
See 2 more Smart Citations